S–H rotamerization via tunneling in a thiol form of thioacetamide. Issue 31 (5th July 2019) - Góbi, Sándor; Nunes, Cláudio M.; Reva, Igor; Tarczay, György; Fausto, Rui
Abstract : Rotamerization of the S–H group via hydrogen tunneling is reported for the first time. Abstract : Rotamerization of a hydroxyl (O–H) group by tunneling is well-known and has been extensively studied. On the other hand, similar tunneling processes for the thiol (S–H) group have not been reported yet. In this work, the imino-thiol forms of thioacetamide were studied in cryogenic matrices (Ar, Xe) after UV-irradiation of the common amino-thione form of the compound. Four different imino-thiol forms were generated, corresponding to the cis or trans thiol (C /T ) conformers of the two imino isomers ( syn and anti ;s /a ). Noteworthy, the syn - cis (sC ) imino-thiol form was found to convert spontaneously to the syn - trans (sT ) form (with a half-life of 80 min), in a process whose reaction rate is independent of the temperature ( i.e., at 11 or 20 K). Such conformational transformation represents the first experimental observation of an S–H rotamerization occurring by tunneling. Computations based on the Wentzel–Kramers–Brillouin formalism predict a tunneling half-life for the S–H rotamerization of syn -iminosC tosT on the time scale of minutes, in agreement with the experimental observations.